Accurate Numerical Integration Method Using Magnetic Flux and Electric Charge for Electromagnetic Transient Simulations - Tanaka, Yohei; Baba, Yoshihiro (IEEE transactions on electromagnetic compatibility, 2025)
In electromagnetic transient (EMT) simulations of electrical and electronic circuits, the compact scheme (CS) is one of the numerical integration methods that can suppress numerical oscillations arising from step-like discontinuous currents or voltages. However, while CS suppresses numerical oscillations effectively, it has difficulty in accurately dealing with switching events in fixed-time step simulations, similar to other conventional methods. To address this problem, this study extends the concept of CS to present a numerical integration method using magnetic flux and electric charge instead of derivative values. The proposed method preserves one-stage and oscillation-free characteristics while allowing for high-accuracy simulation of switching events. The distinctive features of the proposed method are then demonstrated through some simulation cases.